Changes in physical fitness and nutritional status of schoolchildren in a period of 30 years (1980-2010) - Ferrari,Gerson Luis de Moraes (2015)
Objective: To analyze and compare the changes in physical fitness according to the nutritional status and gender of schoolchildren during a period of 30 years (1980-2010). Methods: Four cross-sectional evaluations were performed every 10 years in a period of 30 years from 1978 to 1980 (baseline), 1988-1990 (10 years), 1998-2000 (20 years) and 2008-2010 (30 years). The sample consisted of 1291 schoolchildren (188 in baseline, 307 in 10 years; 375 in 20 years; 421 in 30 years) of 10 and 11 years old. The variables assessed were: body weight (kg), height (cm), upper limb strength (ULS; kg), lower limb strength (LLS; cm), agility (seconds) and velocity (seconds). Schoolchildren were classified as normal weight and overweight according to World Health Organization reference of body mass index for age and gender. Comparisons among periods applied ANOVA followed by Bonferroni test, with a significance level set at of p<0.01. Variation between baseline and 30 years was assessed by the percentage delta. Seven different percentile values were presented for each variable. Results: In eutrophic boys and girls, mean values of ULS (−16.7%; −3.2%), agility (−1.5%; −1.6%) decreased significantly after 30 years (p<0.001). In the overweight boys and girls, only the average ULS (−15.5%; −12.5%) decreased significantly over time (p<0.001). After 30 years, the ULS percentile changed in boys. Conclusions: The decline in physical fitness was greater in schoolchildren with normal weight than in those with overweight.